Guilt by association - what is the true risk of malignancy in children treated with etanercept for JIA? - Cron Randy Q; Beukelman Timothy (BMC, 2010)
Abstract Recently, the Food and Drug Administration placed a "black box" label on etanercept, and other tumor necrosis factor inhibitors used to treat childhood arthritis, warning of the risk of malignancies. The Food and Drug Administration made their decision based on a review of 48 cases of malignancies identified worldwide in children treated with tumor necrosis factor inhibitors for inflammatory bowel disease, sarcoidosis, and juvenile idiopathic arthritis. Recently, an article in Pediatric Rheumatology demonstrated that there may not be an increased risk of cancer in children with juvenile idiopathic arthritis treated specifically with the tumor necrosis factor receptor fusion protein, etanercept. There are many confounding issues regarding whether or not etanercept increases the risk of malignancy, specifically lymphomas, above the background rate of cancer in children with juvenile idiopathic arthritis who are not being treated with biologic agents. Whether or not it was appropriate for the Food and Drug Administration to lump cancer patients with underlying granulomatous diseases (inflammatory bowel disease and sarcoidosis) with children with juvenile idiopathic arthritis is explored herein. Moreover, the amalgamation of etanercept with anti-tumor necrosis factor monoclonal antibodies (adalimumab and infliximab) is another point of contention. What is clear is that there is much that is currently unknown to be able to convincingly demonstrate a substantial risk of cancer in children with juvenile idiopathic arthritis treated with etanercept. Conversely, there is ample evidence demonstrating remarkable benefit of etanercept in treating juvenile idiopathic arthritis. Physicians treating childhood arthritis should weigh these potential risks and benefits with patients and their families discussing the current limitations in available data regarding the risk of cancer in children treated with etanercept for juvenile idiopathic arthritis.